Functional recovery 2-years after hospitalization for COVID-19: Insights from the COREG-FR extension study - Marla Beauchamp; Christopher Farley; Renata Kirkwood; Aaron Jones; Terence Ho; MyLinh Duong; Parminder Raina; Jinhui Ma (PLoS ONE, 2025)
Introduction COVID-19 infection can lead to multi-organ dysfunction, which has been shown to contribute to the physical disability seen in people after hospital discharge. We aimed to understand the effects of hospitalization for COVID-19 on mobility, cognition, and daily activities over 24-months of follow up. Materials and methods This was a 24-month extension of the COREG-FR prospective cohort study (NCT04602260). We enrolled consecutive adult patients (≥18 years) with lab confirmed SARS-Cov-2 infection who were admitted to five Ontario, Canada hospitals between August 21, 2020, and December 21, 2021. Patients were excluded if they resided in an institution (e.g., long term care facility), had severe premorbid physical function limitations (e.g., unable to stand independently) or had cognitive impairment which limited their ability to complete follow-up assessment. We assessed mobility and cognitive status using the Activity Measure for Post-Acute Care (AM-PAC) Basic Mobility Domain and Cognitive Domain, respectively. Deficits from premorbid status were determined using the minimal clinically important differences in mobility (≥ 3.3) and cognition (≥ 5.5). We also asked participants how much their COVID-19 recovery affected their daily activities within the preceding week with response options from ‘not at all’ to ‘all the time’. Results Among the 215 participants who participated 12-months after hospital discharge, 170 (79%) consented to the 24-month follow-up. The mean (standard deviation) age was 61.2 (12.7) years and 54% (n = 91) of participants who were male. Compared to pre-morbid function, mobility and cognitive deficits were present in 57% and 41% of participants, respectively. Furthermore, 59% of participants reported COVID-19 continued to impact their daily activities. Conclusion At 24-months after hospitalization for COVID-19, many participants experience persistent mobility and cognitive deficits. Future work should aim to develop comprehensive rehabilitation strategies for those recovering from COVID-19 which target mobility and cognitive function.